CXCL16 inhibits epithelial regeneration and promotes fibrosis during the progression of radiation enteritis. Issue 2 (12th December 2022) - Cui, Yanmei; Wu, Haiyong; Liu, Zhihang; Ma, Tenghui; Liang, Wenfeng; Zeng, Qingzhi; Chen, Daici; Qin, Qiyuan; Huang, Binjie; Wang, Michael Hu; Huang, Xiaoyan; He, Yanjiong; et al.
Abstract: Radiation enteritis (RE) is a prevalent complication of radiotherapy for pelvic malignant tumors, characterized by severe intestinal epithelial destruction and progressive submucosal fibrosis. However, little is known about the pathogenesis of this disease, and so far, there is no specific targeted therapy. Here, we report that CXCL16 is upregulated in the injured intestinal tissues of RE patients and in a mouse model. Genetic deletion of Cxcl16 mitigates fibrosis and promotes intestinal stem cell‐mediated epithelial regeneration after radiation injury in mice. Mechanistically, CXCL16 functions on myofibroblasts through its receptor CXCR6 and activates JAK3/STAT3 signaling to promote fibrosis and, at the same time, to transcriptionally modulate the levels of BMP4 and hepatocyte growth factor (HGF) in myofibroblasts. Moreover, we find that CXCL16 and CXCR6 auto‐ and cross‐regulate themselves in positive feedback loops. Treatment with CXCL16 neutralizing monoclonal antibody attenuates fibrosis and improves the epithelial repair in RE mouse model. Our findings emphasize the important role of CXCL16 in the progression of RE and suggest that CXCL16 signaling could be a potential therapeutic target for RE. © 2022 The Pathological Society of Great Britain and Ireland.